Modelo ProLab: FruNatural batidos rápidos y nutritivos con oca, amaranto, camu camu endulzado de panela para desayunos activos - Arce Otoya, Miguel Ernesto (2024)
In Peru, the growing omission of breakfast among workers, driven by fast-paced urban life and job demands, raises nutritional and public health concerns. That skipping breakfast is associated with adverse effects on cognitive function, metabolism, mood, and an amplified risk of chronic sicknesses (Smith, et al., 1999; Cahill, et al., 2013; Kaemena, 2022). The Ministry of Health of Peru (2017) also highlights the risks of prolonged fasting in vulnerable groups, directly challenging the UN Sustainable Development Goals: SDG 8 and SDG 12. Six key needs were identified for Marcelo, the user profile: accessibility to healthy options, balance between nutrition and taste, nutritional education and support, affordability of healthy products, motivation and visible results, and integration of healthy eating into the family lifestyle. FruNatural offers quick and nutritious smoothies, featuring native ingredients such as oca, amaranth, camu camu, and panela, ideal for active breakfasts. This solution addresses Marcelo's needs and helps mitigate health problems associated with the omission of breakfast in the working population of Peru. The initial investment for FruNatural is S/ 251,375, which includes working capital for the first year. With a financing structure of 40% from shareholders and 60% from debt, the weighted average cost of capital (WACC) is calculated at 9.82%. This factor contributes to a projected Net Present Value (NPV) of S/ 2,215,520 based on product sales over a five- year period. FruNatural emerges as an innovative and viable solution to address a significant public health issue in Peru.